Simultaneous integrated boost concepts in definitive radiation therapy for esophageal cancer: outcomes and toxicity - Ristau, Jonas; Thiel, Manfred; Katayama, Sonja; Schlampp, Ingmar; Uzun-Lang, Kristin; Häfner, Matthias; Herfarth, Klaus; Debus, Jürgen; Körber, Stefan A. (Radiation oncology, 2021)
Radiation therapy and chemoradiation therapy play a major role in the definitive management of esophageal cancer. Survival in esophageal cancer patients is still relatively poor, mostly due to high rates of local recurrence and distant metastases. It is hypothesized that dose escalation in radiotherapy could improve outcomes. Therefore, this retrospective analysis aimed to investigate the outcomes and toxicity in patients treated with local dose escalation by means of using simultaneous integrated boost concepts.
Gesehen am 23.03.2021